The Extent Of Social Media Practices In Malaysian Sme: Migrating From Adoption To Measurement - Md Jania, Noraniza; Zakaria, Mohd Hafiz; Maksom, Zulisman; M. Haniff, Md. Shariff (School of Social Sciences, USM, 2017)
Social media is leveraged by businesses at a discernible pace. Most often social media is used to instill brand awareness, to stimulate communication, to facilitate relationships, to spur information exchange and innovation, to track customers’ voice, and so forth. Despite the increasing imperative to the varieties of business routines, the measurement aspects of social media marketing initiatives are limitedly discussed. Furthermore, the literature has found the lack of firms’ sensitivity to measurement activities or success indicators for their social media marketing investments. The purpose of this paper is to discuss the extent of social media measurement practices in business from two contexts: first, in the prominent platform of social networking sites, and second, in the perspective of Malaysian SMEs. A preliminary investigation was conducted with 30 respondents from selected industry groups in services and manufacturing sectors to acquire the well-informed data in the SMEs of the southern region. The findings have shaped several themes of social media adoption and evaluation practices for Malaysian SMEs. Accordingly, the barriers and future directions of measurement efforts on social media platform are discussed.